Icarifil, a Natural Mixture Based on L-Citrulline and L-Carnitine as a Novel Multicomponent Nutraceutical to Modulate ROS and PDE5 - Chiara Amante; Chiara De Soricellis; Gianni Luccheo; Anna Di Vernieri; Luigi Luccheo; Giovanni Falcone; Pasquale Del Gaudio (Applied Sciences, 2023)
Erectile dysfunction (ED) is a pathology that affects both an individual’s life and their partner’s, representing an increasing health concern. Currently, phosphodiesterase type 5 inhibitors (PDE5i) remain the first-line therapy for erectile dysfunction, and no other drugs are approved. However, the high cost of these drugs and related adverse events limit their use. Since the concept of nutraceuticals has been extended from health promotion to the treatment of diseases, in this work, a novel mixture of different natural substances named Icarifil (L-Citrulline, L-Carnitine, Eruca vesicaria, Panax ginseng, Tribulus terrestris, Turnera diffusa, Taurine, Vitamin E, Zinc) was studied to verify its ability to increase the proliferation of muscle epithelium cells and cell turgor, as well as, due to containing antioxidants, its ability to reduce the amount of ROS that are mediators in the pathophysiological process of ED. Moreover, Icarifil showed efficacy in inhibiting PDE5 levels higher than 65% compared to the control and 35% compared to the mixture of L-Citrulline and L-Carnitine, the major components of the formulation. In association with the low dosage of a phosphodiesterase (PDE) inhibitor (tadalafil), the inhibitory capacity of tadalafil was significantly increased and comparable to high-dosage drug response, promoting the possibility of reducing the daily dosage of the drug and consequently its adverse effects.